Lycra arm splints in conjunction with goal-directed training can improve movement in children with cerebral palsy - Elliott, Catherine; Reid, S.; Alderson, J.; Elliott, B. (2011)
Objectives: To investigate the effects of lycra® arm splint wear on goal attainment and three dimensional (3D) kinematics of the upper limb and trunk in children with cerebral palsy (CP). Design: Randomised clinical trial whereby participants were randomised to parallel groups with waiting list control. Participants: Sixteen children with CP (hypertonia) aged 9 to14 years. Intervention: Three months lycra arm splint wear combined with goal directed training. Main outcome measure: Goal attainment scale, and 3D upper limb and trunk kinematics across four upper limb movement tasks. Results: 17/18 children achieved their movement goals following three months of splinting. Selected joint kinematics improved on immediate splint application. Further improvements in joint kinematics were demonstrated following 3months of splint wear, particularly in elbow extension, shoulder flexion and abduction and in thorax flexion. Only improvements in movement compensations at the thorax remained following removal of the splint. Conclusions: The lycra® arm splint, made a quantifiable change to the attainment of movement goals of importance to the child. Furthermore, improvements were demonstrated in selected maximum range of movement and joint kinematics during functional tasks at the elbow and shoulder joints and thorax segment in children with CP. © 2011 - IOS Press and the authors. All rights reserved.